SISTEM VENTILASI DALAM KAPAL - Utomo, Budi (Diponegoro University, 2007)
Ventilation in ships is a process substitute dirty air in a hold of ship with fresh air from outside. If meansfor keep air in compartment always clean or fresh to make people comfort and to limit influence destructionpart of ship also rattenness of cargo that caused by too high dampness of the air.Ventilation system in ships differences two kind, that are natural ventilation system and mechanicalventilation system.Natural ventilation principles uses movement or flow of natural air, for example there are wind or air flowthat caused by symptom of air rising because temperature different. Where as on mechanical ventilationsystem the principles same with natural ventilation system, but air movement helped by ventilator oranother similar tools that rotation in the tube.